Implementasi Program Pelatihan Ex-Buruh Rokok dari Penggunaan Dana Bagi Hasil Cukai Hasil Tembakau (DBHCHT) Kabupaten Kudus - Azmi Hikmawati; Priyatno Harsasto; Wahid Abdulrahman (Journal of Politic and Government Studies, 2017)
The number of tobacco industry in Kudus Regency is more lessen. This decrease in the number of tobacco industries and the amount of production is considered a success of the government suppressing the Tobacco Industries. This condition leads to employee layoff and causing them to be an unemployed. In accordance with government regulations in term of Tobacco Excise Revenue Sharing Fund management, it is used for funding group activities, one of them is social development programs. Ministry of Labor, Industries, Cooperatives and SMEs of Kudus Regency as the recipient of the allocation fund, carry out duties and authorities for the community around the tobacco industries. This training program is also held for former tobacco workers in order to reduce unemployment and to prompt the economic growth through work abilities and skills training program.This research was conducted by using qualitative research method. Data collection used in this research is by interview, observation and documentation with the Ministry of Labor, Industries, Cooperatives and SMEs of Kudus Regency and Lecturer Faculty of Economics Muria Kudus University.The results show that the implementation of the training programs still not according to former workers and the community around the tobacco industries needs to manage the Tobacco Excise Revenue Sharing Fund. The lack of cooperation between tobacco industries and the government regarding data of number of companies that are still active, number of labor and no renewals of data of production. The government run the training programs without regarding the need of instructions and technical guide of the program implementation. The government refers more to the budget which has been set to run the training programs.The government could make an instruction of the training program implementation, even though its implementation is exactly similiar for every year. The government needs to cooperate in order to record who has been layoff from the tobacco industries to join the training programs. The community around the tobacco industries have to take the advantages to develop a private business.Keywords: Implementation, Training Program, Former Cigarette Workers